A review of the role of public health informatics in healthcare - Aziz, Hassan (2017)
Recognized as information intensive, healthcare requires timely, accurate information from many different sources generated by health information systems (HIS). With the availability of information technology in today's world and its integration in healthcare systems; the term “Public Health Informatics (PHI)” was coined and used. The main focus of PHI is the use of information science and technology for promoting population health rather than of individuals. PHI has a disease prevention rather than treatment focus in order to prevent chain of events or disease spread. Moreover, PHI often operates at the level of government rather than at the private sector. This review article provides an overview of the field of PHI and compares between paper based surveillance system and Public Health Information Networks (PHIN). The current trends and future challenges of applying PHI systems in KSA were also reported.